The Pandemic as a Conservation Marketing Intervention: Could COVID-19 Lower Global Demand for Wildlife Products? - Moorhouse, Tom P.; D'Cruze, Neil C.; Macdonald, David W. (Frontiers in Ecology and Evolution, 2021)
We wished to assess whether the COVID-19 pandemic, thought to have a zoonotic origin, may lead to a reduction in consumer demand for wildlife products. In 2018 we surveyed the effect of demand reduction messaging on consumers’ desire to own exotic pets with 1,000 respondents in each of Brazil, China, the USA and Vietnam. In July 2020, during the pandemic, we repeated the survey with 100 new respondents in each country. Mean desire to own a given exotic pet was 40-60% lower in 2020 during the pandemic, but only for respondents from Brazil, China and the USA, and only for the group of respondents who had high a priori purchase likelihoods: those who had already owned an exotic pet. The stated desire to own of non-owners was no different in 2020, but this group already had extremely low purchase likelihoods. Vietnamese pet owners, in contrast to those in other countries, exhibited higher purchase desire during the pandemic than previously. We speculate that this arose because Vietnam has a long history of dealing with epidemic disease, had no COVID-19 related deaths by the time of survey, and so population uncertainty about the consequences of exotic pet ownership may have decreased. While limited, our initial evidence indicates that the global pandemic is unlikely to permanently curb demand for wildlife products.